(untitled) (Socious Journal, 2025)
This study examines the socio-economic impacts of agricultural land conversion into industrial areas in rural Indonesia using qualitative methods based on literature. This transformation drives a process of de-agrarianization that alters income sources, work structures, and social identities in rural communities. Land conversion triggers diversification of livelihood strategies, increases land prices, and shifts in asset ownership, but compensation that is not managed productively has the potential to undermine economic independence. The impact on food security and sovereignty is significant, as reduced harvested areas reduce local production and increase dependence on external supplies. The shift in values from a subsistence ethos to an industrial logic triggers cultural lag, erodes social cohesion, and changes gender roles and domestic work patterns. The presence of migrant workers and the demand for industrial skills create new social stratifications that widen inequalities. Institutional factors such as transparency in compensation and strengthening village institutions determine whether this change leads to upward mobility or structural poverty. This study emphasizes the need for mitigation strategies that combine structural and cultural dimensions, including land protection, skills development, and strengthening social capital, to ensure rural industrialization is inclusive and does not deepen inequality. These findings are expected to inform equitable and sustainable village development policies